The Impact of Cultural Experience of Two Translators on Literary Translation - Altmann, Christian Jakob (Research in Language, 2020)
The main focus of this paper is to examine the translation strategies of the translators of Herta Müller’s novel Atemschaukel, Radka Denemarková (Czech) and Katarzyna Leszczyńska (Polish). The aim is to find out to what extent the cultural experience of these translators, consisting of biographical, artistic and linguistic aspects, has influenced the translations. Important in this context is the transculturalism of the author Herta Müller. She uses idiomatic expressions and uses borrowings and a multitude of neologisms, the translation of which is influenced to varying degrees by the cultural experience of the translators in their search for equivalence at the level of expression.